Optimizing the Intensive Care Treatment of Delirium in Patients with 1,4-butanediol Intoxication - A. G. Sinenchenko; A. N. Lodyagin; B. V. Butotsyrenov (Общая реаниматология)
The aim of the study is to explore the best intensive care strategies for acute 1,4-butanediol poisoning complicated by post-intoxication delirium.Materials and methods. The data of the laboratory testing and treatment of 40 men with acute severe poisoning with 1,4-butanediol, complicated by post-intoxication delirium were analyzed. Twenty patients received succinate-containing drug, others were treated with conventional methods. The control group included 18 healthy male patients aged 25 to 40 years. Clinical course of delirium, parameters of glutathione system and lipid peroxidation in patients' red blood cells, oxygen transport function (by indirect calorimetry), gammahydroxybutyric acid level in the biological fluids by gas chromatography/mass spectrometry were evaluated during the study.Results. An increases in levels of reduced glutathione by 50.3% by day 7 (from 3.68±0.57 to 5.53±0.35 pmol/g), hemoglobin (Hb), antioxidant enzymes and glutathione reduction enzymes were found; glucose-6-phosphate dehydrogenase increased by 17,1% (from 3.68±0.26 to 4.31±0.41 pmol/g Hb) and glutathione reductase increased by 15% (from 174.1±16.3 to 200.2±4.11 pmol/min/g Hb). At the same time, the MDA lipid peroxidation system activation was decreased by 41.9% (from 7.78±1.06 to 4.52±0.28 nmol/g Hb).Conclusion. The obtained data proved high efficacy of a succinate-containing drug in slowing down the progression of post-intoxication delirium through increasing the level of the main cellular antioxidant, the reduced glutathione.